IMPROVING THE EFFICIENCY OF PAYROLL AND WAGE PROCESSES IN SURABAYA'S CREATIVE INDUSTRIES: COULD MANAGEMENT ACCOUNTING INFORMATION SYSTEM DO IT? - Zaman, Komarun; Adhitya Pratama, Devangga Putra (Sekolah tinggi ilmu ekonomi pemuda, 2023)
The purpose of this study was to analyze and find out about the accounting information system in the process of payroll and wages. In addition, the purpose of this study is also to determine the effect of an effective and efficient payroll and payroll accounting information system, thus facilitating the payroll and remuneration process. The research method used in the research of payroll and wage accounting information systems is to use qualitative descriptive research methods and literature. An Accounting Information System (AIS) is a system designed to collect and display accounting information so that accountants and company executives can make informed decisions. The results of this study indicate that every government agency needs to implement public sector accounting because it can simplify and improve the quality of presenting financial reports.